Analisis Pelaporan Keuangan Segmentasi Pada PT. Mayora Indah Tbk - Beni Wahyu Ariyudi; Fahmi Fadilla; Aulia Rahmi; Rama Gita Suci (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
Disclosure of financial statements is one of the things that must be done by companies that have gone public. This study aims to analyze the performance of PT. Mayora Indah Tbk through its 2018-2022 financial statements which are listed on the Indonesia Stock Exchange (IDX) with PSAK No. 5. This study uses qualitative methods while the sampling technique uses a porposive sampling technique. Sampling is based on data from the financial statements of the PT segment. Mayora Indah Tbk which is divided into three segments, namely packaged processed food, packaged processed drinks and financial services business. Based on research that has been carried out through a ten percent test on revenue, profit and loss, and assets of PT. Mayora Indah Tbk makes the processed food and packaged processed beverage segments reportable, while the financial services business segment cannot be reported because it does not meet the ten percent test conducted on the three business segments of PT. Mayora Indah Tbk.